2001
DOI: 10.1023/a:1014227231130
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Free fatty acids (FFA) in cerebrospinal fluid (CSF) are well-recognized markers of brain damage in animal studies. Information is limited regarding human CSF in both normal and pathological conditions. Samples of CSF from 73 patients, who had undergone lumbar puncture for medically indicated reasons, came from a core laboratory upon completion of ordered tests. Using high performance liquid chromatography, mean FFA concentrations (microg/L +/- SEM) were: arachidonic 26.14 +/- 3.44; docosahexaenoic 60.74 +/- 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Further supporting reports demonstrated that in traumatic brain injury, free fatty acid (FFA) levels increase significantly in the cerebrospinal fluid (CSF), and are recognized as markers of brain injury. In particular, the concentration of palmitate almost doubled as compared to control, above 1100 μg/L in the CSF of traumatic brain injury versus around 600 μg/L in control (Pilitsis et al, 2003; Pilitsis et al, 2001; Zamir et al, 1991). FFAs in plasma can cross the blood-brain barrier (Dhopeshwarkar and Mead, 1973; Smith and Nagura, 2001), and high fat diets increase the uptake of fatty acids by the brain from the plasma (Karmi et al, 2010; Wang et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
“…Further supporting reports demonstrated that in traumatic brain injury, free fatty acid (FFA) levels increase significantly in the cerebrospinal fluid (CSF), and are recognized as markers of brain injury. In particular, the concentration of palmitate almost doubled as compared to control, above 1100 μg/L in the CSF of traumatic brain injury versus around 600 μg/L in control (Pilitsis et al, 2003; Pilitsis et al, 2001; Zamir et al, 1991). FFAs in plasma can cross the blood-brain barrier (Dhopeshwarkar and Mead, 1973; Smith and Nagura, 2001), and high fat diets increase the uptake of fatty acids by the brain from the plasma (Karmi et al, 2010; Wang et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
“…69 FFA increases have also been observed in the rat brain following CCI 21 as well as in the CSF of TBI patients. 70,71 An increase in FFAs is known to accompany cellular injury events such as uncoupling of oxidative phosphorylation, exacerbating the disruption of ion balance and aggregation of oxidative metabolites. 72 The disruption of calcium ion homeostasis in combination with energy depletion in the brain following injury leads to the activation of phospholipases A 2 and C, which causes the release of FFAs from membrane phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Hashimoto and colleagues suggested that DHA’s effects on Aβ oligomerization might be independent of micelle formation (since they occur below critical micelle concentration) and revolve around the disruption of hydrophobic intra- and inter-chain amino acid interactions (Hashimoto et al, 2009; Hashimoto et al, 2008; Hossain et al, 2009). However, directly extrapolating these in vitro findings to in vivo settings remains challenging given that the free DHA concentrations necessary to modulate Aβ aggregation in vitro (10 μM to 50 μM) (Hashimoto et al, 2009; Hashimoto et al, 2008; Hossain et al, 2009; Johansson et al, 2007) are far higher than those measured from human CSF (185 nM; Pilitsis et al, 2001). …”
Section: Discussionmentioning
confidence: 99%